Metode Pendidikan dalam Hadis Nabi Muhammad SAW: Analisis Konsep dan Implementasi - Ahmad Nizal Kafi Manan; Shobrun Jamil; Marizka Hana Humaira; Marsha Ashfiya Lailashufa; Nabilla Hapsari (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to examine educational methods in the hadiths of Prophet Muhammad (PBUH) and their relevance to modern education. Using a qualitative method based on library studies and content analysis, the research finds that the hadiths contain methods of exemplary behavior, dialogue, motivation, storytelling, and habituation. These methods have been proven relevant for character building and improving the quality of learning. The study concludes that the educational approach in the hadiths is practical and can be effectively integrated into contemporary educational contexts.